Prevalence of non-alcoholic fatty liver disease among obese children in North Kerala, India - G., Reetha; P., Mahesh (International Journal of Contemporary Pediatrics, 2017)
Background: Obesity and related co-morbidities are increasing at an alarming pace all over the world. Non-alcoholic fatty liver disease (NAFLD) is the asymptomatic involvement of the liver mainly seen in obese individuals. NAFLD can progress to chronic liver disease and has to be identified early. The aims of our study were to determine the prevalence of nonalcoholic fatty liver disease among obese children in our local population. To determine the prevalence of abnormal liver enzymes in obese children. Methods: Cross sectional descriptive study in a tertiary care center among children aged 5-18 years for a 1 year period. NAFLD was diagnosed based on ultrasonography. Alanine amino transferase more than 40IU/l was taken as abnormal. Results: A total of 65 patients were enrolled in the study. The prevalence of NAFLD in the study group was 60%. 20% had elevated alanine amino transferase levels. Conclusions: The prevalence of fatty liver in Kerala is comparable to that in the West. Since this is a public health issue more population based studies are needed on a larger group to find out the exact magnitude of the problem.